Is it good to be too light? Birth weight thresholds in hospital reimbursement systems - Simon Reif; Sebastian Wichert; Amelie Wuppermann (Friedrich-Alexander-Universität Erlangen-Nürnberg, Institute for Economics, 2017)
Birth weight manipulation is common in per-case hospital reimbursement systems, in which hospitals receive more money for otherwise equal newborns with birth weight just below compared to just above specific birth weight thresholds. As hospitals receive more money for cases with weight below the thresholds, having a (reported) weight below a threshold could benefit the newborn. Also, these reimbursement thresholds overlap with diagnostic thresholds that have been shown to affect the quantity and quality of care that newborns receive. Based on the universe of hospital births in Germany from the years 2005-2011, we investigate whether weight below reimbursement relevant thresholds triggers different quantity and quality of care. We find that this is not the case, suggesting that hospitals' financial incentives with respect to birth weight do not directly impact the care that newborns receive.
Keywords: I11; I18; 330; neonatal care; DRG upcoding; quantity & quality of care